Designing an Early Detection System for Agricultural Land to Reduce the Risk of Crop Failure Based on Information Technology - Edy Atthoillah; Nadia Ayu Safitri; Wishal Azharyan Al Hisyam; Muhammad Sibyan Nafil Ilmi; Asbi Solihin; Dafit Ari Prasetyo (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Crop failures in Indonesia still occur frequently and become a source of problems due to the reduction of food supplies for the community. One of the causes of crop failure is the decline in soil quality due to nutrient content, which is rarely detected by farmers. However, the land quality analysis process that has been carried out so far still tends to take a long time and incur high costs. Therefore, it is necessary to create technology that is expected to be able to detect land quality directly, quickly, and easily. PKM- KC Soil Nutrient Monitoring is designed by creating hardware that can analyze moisture, pH, temperature, and essential macro nutrients, namely nitrogen, phosphorus, and potassium. Additionally, software that can process data and produce results in the form of land quality, land improvement recommendations, and suggested crop commodities. This Soil Nutrient Monitoring tool has been tested and calibrated with an accuracy level of 95%. This tool successfully processes data from hardware in the form of temperature, pH, humidity, and NPK sent via a Bluetooth Low Energy network to software that produces outputs in the form of land quality, land improvement recommendations, and suggested crop commodities